Heavy Metal Pollution, Selection, and Genome Size: The Species of the Žerjav Study Revisited with Flow Cytometry. (31st May 2010) - Temsch, Eva M.; Temsch, Wilhelm; Ehrendorfer-Schratt, Luise; Greilhuber, Johann
Abstract : The Death Valley at Žerjav in northern Slovenia exhibits a gradient of heavy metal pollution in the soil with severe consequences for species richness and composition along this gradient. Recently, a progressive loss of large-genome species in parallel with increasing concentrations of heavy metals has been shown. Here, we have measured the genome size of a near-complete sample of these species with flow cytometry and analysed the correlation of heavy metal pollution with the C- and Cx-values assigned to the test plots. The method of probability analysis was a hypergeometric distribution method. We confirm, on a different methodological basis than previously, that along the pollution gradient, species with high C- and Cx-values are increasingly underrepresented. This lends support to the "large genome constraint hypothesis", predicting that plants with large genomes are at a disadvantage under all aspects of evolution, ecology, and phenotype, because junk DNA imposes a load to the organism.